Myopic choroidal neovascularization with dilated choroid vessels is prone to progression into subretinal fibrosis following anti-vascular endothelial growth factor therapy: a retrospective study - Xiangjun She; Qiwei Cai; Wangjing Yao; Shixin Zhao; Zhe Lv; Suyan Shan; Jiwei Tao; Yun Zhang (Eye and Vision)
Abstract Background This retrospective study aimed to identify risk factors for subretinal fibrosis (SF) and evaluate the response to anti-vascular endothelial growth factor (anti-VEGF) therapy in patients with myopic choroidal neovascularization (mCNV), with a specific focus on the role of dilated choroidal vessels (DCVs) in disease progression. Methods In this retrospective study, patients with high myopia (spherical equivalent < −6.0 D, pathological myopia, Asian ethnicity) and active mCNV lesions, diagnosed between 2021 to 2023, were evaluated. The location of DCVs and mCNV was assessed, and macular thickness, submacular choroid thickness, best-corrected visual acuity, CNV area, and flow density were measured at baseline and during follow-up. The presence of posterior staphyloma was evaluated at baseline. SF around the mCNV was evaluated lesions during follow-up. The time to SF detection was recorded using survival analysis. Risk factors for SF were analyzed using Kaplan–Meier and multivariable Cox regression analyses. Results A total of 46 eyes from 46 patients were included, with a mean age of 54.17 ± 14.37 years, and a baseline spherical equivalent of 12.36 ± 3.21 D. The logarithm of the minimum angle of resolution for the mean visual acuity was 0.70 (0.40–1.30), and the mean macular thickness was 313.11 ± 63.57 μm at baseline. DCV was detected in 29 of the 46 eyes (63.0%), and the median time to detect SF was 43.41 [95% confidence interval (CI): 37.27–49.55] months. Multivariable Cox regression analysis identified submacular DCV [hazard ratio (HR): 14.93, 95% CI: 5.72–38.91, P < 0.001) and absence of posterior staphyloma (HR: 43.48, 95% CI: 12.15–156.32, P = 0.002) as independent predictors of SF. The presence of DCV under the fovea compared to the peripheral zone achieved a poorer therapeutic response and was prone to progress to SF after anti-VEGF therapy (P = 0.041). Conclusions Submacular DCV is associated with poor therapeutic response to anti-VEGF therapy and an increased risk of SF in patients with mCNV.